The autophagic regulation of rosiglitazone-promoted adipocyte browning - Li, Yue; Zheng, Wanqing; Li, Xinhang; Lue, Zhengwei; Liu, Yun; Wu, Jiaying; Zhang, Xiangnan (Frontiers in Pharmacology, 2024)
Objective: Browning of white adipocytes is considered an efficient approach to combat obesity. Rosiglitazone induces the thermogenetic program of white adipocytes, but the underlying mechanisms remain elusive. Methods: Expression levels of browning and autophagy flux markers were detected by real-time PCR and immunoblotting. H&E and Oil Red O staining were performed to evaluate the lipid droplets area. Nuclear protein extraction and immunoprecipitation were used to detect the proteins interaction. Results: In this study, we reported that rosiglitazone promoted adipocyte browning and inhibited autophagy. Rapamycin, an autophagy inducer, reversed adipocyte browning induced by rosiglitazone. Autophagy inhibition by rosiglitazone does not prevent mitochondrial clearance, which was considered to promote adipose whitening. Instead, autophagy inhibition increased p62 nuclear translocation and stabilized the PPARγ–RXRα heterodimer, which is an essential transcription factor for adipocyte browning. We found that rosiglitazone activated NRF2 in mature adipocytes. Inhibition of NRF2 by ML385 reversed autophagy inhibition and the pro-browning effect of rosiglitazone. Conclusion: Our study linked autophagy inhibition with rosiglitazone-promoted browning of adipocytes and provided a mechanistic insight into the pharmacological effects of rosiglitazone.